2000
DOI: 10.1046/j.1523-1755.2000.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the results of renal transplantation from non–heart-beating, conventional cadaveric, and living donors

Abstract: Despite being associated with poor initial graft function, the long-term allograft survival of NHBD kidneys does not differ significantly from the results of HBD and LD transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
122
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 14 publications
5
122
0
4
Order By: Relevance
“…[3][4][5][12][13][14] Other studies have reported poor renal function with such prolonged ischemia times. 14,15 It would seem that kidneys with tumours amenable to partial nephrectomy may not be subjected to the same global stress as kidneys with major trauma or physiologic events surrounding the death of cadaveric kidney donors and hence may tolerate longer WIT.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][12][13][14] Other studies have reported poor renal function with such prolonged ischemia times. 14,15 It would seem that kidneys with tumours amenable to partial nephrectomy may not be subjected to the same global stress as kidneys with major trauma or physiologic events surrounding the death of cadaveric kidney donors and hence may tolerate longer WIT.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 -19 The effect of kidney graft size and recipient weight (Rw) 20,21 has also been studied; however, the direct impact of matching the Kw itself (which correlates with both glomerular volume and nephron number) 15 to the Rw has been studied only in relatively small cohorts of Ͻ300 patients and only in living donors, 22,23 where the graft does not incur the same accumulating injuries as those from deceased donors.…”
mentioning
confidence: 99%
“…[3][4][5][12][13][14] Other studies have reported poor renal function with such prolonged ischemia times. 14,15 It would seem that kidneys with tumours amenable to partial nephrectomy may not be subjected to the same global stress as kidneys with major trauma or physiologic events surrounding the death of cadaveric kidney donors and hence may tolerate longer WIT.…”
Section: Discussionmentioning
confidence: 99%